Security as an outcome for promoting economic prosperity in the regional economic communities of Africa: Evidence from a panel data analysis. Issue 4 (1st October 2020) - Saba, Charles Shaaba
ABSTRACT: This study investigates the impact of security outcomes on economic prosperity in Africa and its Regional Economic Communities (RECs) using a balanced panel data of 35 African countries and eight RECs for the period 1990–2015. Economic prosperity was measured with real GDP per capita as the proxy while security outcomes was computed from security effectiveness and legitimacy by using principal component analysis. This study employs a panel causality test and the Generalised Method of Moments (GMM) estimation techniques. The empirical results suggest that security outcomes promotes economic prosperity at the continental level and in six RECs. This implies that the security measures used in this study are important in providing an enabling environment for economic activities and opportunities despite the numerous security challenges facing the continent. Thus, an appropriate policy to improve and strengthen the security sector should be given priority in the RECS and across the entire continent.